Predicting user acceptance of collaborative technologies: An extension of the technology acceptance model for e-learning - Cheung, Ronnie; Vogel, Doug (Computers and education, 2013)
Collaborative technologies support group work in project-based environments. In this study, we enhance the technology acceptance model to explain the factors that influence the acceptance of Google Applications for collaborative learning. The enhanced model was empirically evaluated using survey data collected from 136 students enrolled in a full-time degree program that used Google Applications to support project work. According to the research results, determinants of the technology acceptance model are the major factors influencing the adoption of the technology. In addition, the subjective norm represented by peers is found to significantly moderate the relationship between attitude and intention toward the technology. However, our results do not show a significant effect of subjective norms represented by instructors and mass media on students' intentions to use the technology. The ability to share information in the collaborative learning environment is found to influence intention and behavior toward the Google Applications platform. ► An integrated model is used to explore user acceptance of collaborative technologies. ► The subjects are students employing Google Applications for collaborative learning. ► Use of an enhanced technology acceptance model in this context is successful. ► Major factors driving technology adoption are self-efficacy, sharing, and peer norms. ► Peer norms moderate the relationship between attitude and behavioral intention.